Influence of processing conditions on polymorphism and nanofiber morphology of electroactive poly(vinylidene fluoride) electrospun membranes - Ribeiro, C. (2010)
Poly(vinylidene fluoride) electrospun membranes are obtained from a 20% w/w solution of the polymer in dimethyl formamide. Processing parameters are systematically changed to analyze their influence on fiber morphology, fiber orientation and on the crystallinity and crystal phase of the membranes. The PVDF concentration and travelling distance from the needle to the collector are kept fixed while the influence of the flow rate, needle diameter, applied voltage and rotating collector speed is considered. The study allows concluding that those parameters leading to a higher stretching of the jet or straining of the fibrils during collection favor the formation of the electroactive β-phase while the total crystalline fraction depends only slightly on the electrospinning conditions.